Pentingnya Budaya dan Kearifan Lokal Dalam Pengembangan Dunia Penyiaran di Daerah - Samin, Rumzi (Jurnal Ilmu Administrasi Negara (JUAN), 2015)
Pentingnya Budaya Dan Kearifan Lokal DalamPengembangan Dunia Penyiaran Di Daerah Rumzi Samin (Jurusan Ilmu Administrasi Negara FISIP UMRAH) Abstract: It is ethnic Malay people can be seen as a cultural (culture), not necessarily in genealogy (equation consanguinity). As a civilized creatures must not be separated from the rules and regulations known as the rule of law . Due to wilt synonymous with Islam , the Islamic values become the basic foundation of the indigenous Malay.Sowing wisdom realized by providing an understanding of the layman , explaining in vague and give sense to the people who are still in diapers and knowledge. To discuss something useful let first thought good orbad , do not talk nonsense.Language broadcasting in speaking not considered beforehand good or bad , it will not bring benefits , talks futile just spending time alone , and even bring in contention. Language broadcasting using local languages is a local wisdom used to facilitate understanding of the information submitted and facilitate digestion and kenalaran information so readily accepted by the local community .